2006
DOI: 10.1634/theoncologist.11-5-422
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation in Young Women Undergoing Breast Cancer Therapy

Abstract: After completing this course, the reader will be able to:1. Explain how chemotherapy for breast cancer impacts ovarian function.2. Discuss the incidence of ovarian failure after chemotherapy and list the chemotherapeutic agents most likely to cause loss of fertility in breast cancer patients.3. Describe options for fertility preservation in women undergoing breast cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(166 citation statements)
references
References 148 publications
2
149
0
11
Order By: Relevance
“…The combined 5 years relative survival rate for children with cancer has improved from around 63% for patients diagnosed during the period 1975-1979 to 79% for those diagnosed 1995-1999 [2]. Several chemotherapeutic agents [3] and radiotherapy used in cancer treatment are toxic to the ovaries [4].…”
Section: Introductionmentioning
confidence: 99%
“…The combined 5 years relative survival rate for children with cancer has improved from around 63% for patients diagnosed during the period 1975-1979 to 79% for those diagnosed 1995-1999 [2]. Several chemotherapeutic agents [3] and radiotherapy used in cancer treatment are toxic to the ovaries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid counseling may allow YBCP sufficient time for one or two rounds of egg collection without delaying the start of their cancer treatmeKim et al, 2011). Some investigators have reported that the benefit of GnRH agonist therapy to protection of ovaries is unproven and it should not be offered as individual method of fertility preservation in young breast cancer patient (Sonmezer and Oktay, 2006;Bedoschi et al, 2013). Recent studies suggest that GnRH with chemotherapy in premenopausal women is associated with higher rates of resumption of menses, although it is not associated with improvement in pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…The Oncologist 2012;17:910 -916 www.TheOncologist.com have a negative impact on ovarian reserve and may cause infertility or premature menopause [7][8][9][10]. This has a significant impact on patients' quality of life, with breast cancer survivors rating infertility, premature menopause, and sexual dysfunction highest of the problems experienced since diagnosis [11].…”
Section: Breast Cancermentioning
confidence: 99%